2010
DOI: 10.1177/0272431610376247
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Family Experiences and Perceived Social Support in Young Adulthood

Abstract: Although the protective role of social support is well established in the health literature, antecedents of perceived social support are not well understood. Research on family experiential factors during early adolescence, an important psychosocial developmental period in the life course, represents a promising line of inquiry. Using a sample of young adults in Miami-Dade County, Florida ( N = 1,267) involving longitudinal data spanning 8 years, we evaluated the importance of early adolescent family experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 92 publications
(118 reference statements)
3
20
0
3
Order By: Relevance
“…Family conflict, but not peer aggression or scripts, was related to social support. These findings are consistent with literature suggesting that early negative interactions with family directly impact perceived overall social support later in adolescence (Gayman et al 2011). Findings additionally indicated that family conflict and peer aggression, but not scripts, was related to criminal history.…”
Section: Discussionsupporting
confidence: 92%
“…Family conflict, but not peer aggression or scripts, was related to social support. These findings are consistent with literature suggesting that early negative interactions with family directly impact perceived overall social support later in adolescence (Gayman et al 2011). Findings additionally indicated that family conflict and peer aggression, but not scripts, was related to criminal history.…”
Section: Discussionsupporting
confidence: 92%
“…These findings also suggest that social support mitigates the deleterious effects of stress on heath (Gayman, Turner, Cislo, & Eliassen, 2011) and academic success (Danielsen et al, 2010). Stress is known to be deleterious to health by promoting maladaptive behavioural coping responses (e.g.…”
Section: Introductionmentioning
confidence: 68%
“…Assim, a confi guração familiar vem perdendo relevância em detrimento da relação estabelecida precocemente com os pais. Os efeitos do divórcio dependem mais da maneira que o casal gere todo o processo (Mathew et al, 2011;Orbuch, Thornton, & Cancio, 2000). Por vezes a separação parental leva à conquista de menores confl itos o que pode ser mais benéfi co para os fi lhos em termos de segurança e autonomia comparativamente aos fi lhos que vivem em famílias pautadas por confl itos parentais (Amato, 2010;Moura & Matos, 2008).…”
Section: Discussionunclassified
“…Assim, perante acontecimentos que desencadeiam sentimentos negativos, como poderá ser a dinâmica do processo de divórcio, o indivíduo tende a adotar estratégias que lhe permitam a minimização desse sofrimento (e.g. Amato, 2010;Mathew, Gayman, Turner, Cislo, & Eliassen, 2011 No que diz respeito à capacidade de lidar com eventos geradores de stress, as crianças têm apresentado menos recursos do que adolescentes e adultos, principalmente quando esses eventos implicam as fi guras parentais, situações familiares ou domínio escolar (Lisboa et al, 2002). De acordo com Ramires (2004), os adolescentes enfrentam melhor as transições familiares, pois se encontram mais desenvolvidos em termos afetivos, cognitivos e sociais comparativamente com as crianças.…”
Section: A Individuação E a Confi Guração Familiar No Desenvolvimentounclassified